Karakteristik Pasien Demam Tifoid Di Rumah Sakit Ibnu Sina Makassar - Laode, Mardika Intan Setya Putri; Nasruddin, Hermiaty; Surdam, Zulfiyah; Nurelly, Nurelly; Syahril, Erlin (Wal'afiat Hospital Journal, 2021)
Typhoid fever is an infectious disease caused by the bacterium Salmonella enterica serovar Typhi (S. Typhi). It is estimated that between 350-850 per 100,000 population per year. This disease attacks all ages, some studies argue that the male sex suffers from typhoid fever more because it is influenced by work, environment, and eating and drinking habits. This disease is an endemic disease that is still a health problem in Indonesia due to the lack of deep quality of personal hygiene and environmental sanitation. This study aims to determine, classify and describe the characteristics (age, gender, type of therapy, length of treatment) in typhoid fever patients at Ibnu Sina Hospital Makassar in 2019. This study is a descriptive observational study with a retrospective approach. The population in the study amounted to 490 samples. The sample of this study is secondary data, namely, by taking medical record data, sampling using purposive sampling method and the sample size is obtained as many as 82 samples. ie 15 – 24 years (39.0%), based on the type of therapy, namely type 1 therapy (92.7%) where this type of therapy used 1 type of antibiotic, based on the length of treatment 7 days (90.2%). The conclusion is that the number of typhoid fever sufferers is 82 people with the most gender being male, the highest age is 15-24 years, the most use of therapy using one type of antibiotic is accompanied by the longest length of treatment, which is an average of fewer than 7 days.